Creating heritage in Ubud, Bali - Vickers, Adrian (Wacana, Journal of the Humanities of Indonesia, 2019)
In Bali, heritage is more-or-less synonymous with tradition. The popular view of what constitutes Bali’s heritage tends to focus on the village and wider district of Ubud. Through examining at the strategies employed by the lords of Ubud during the middle part of the twentieth century, we can better understand how the image of heritage sites is created. In the case of Ubud, the construction of centre of tradition was carried out through alliances with local artists and with expatriates, notably Rudolf Bonnet. The latter were able to mobilize publicity and networks to attract resources and elevate the district’s reputation.